The multifrequency low-voltage plasma-beam generator - Antipov, V.S.; Arhipov, A.V.; Bez’yazychny, I.A.; Berezhnaya, I.V.; Kornilov, E.A. (Вопросы атомной науки и техники, 2007)
The authors have submitted the experimental results concerning the excitation of multi-frequency oscillations in the beam-plasma generator based on the helical slow-wave structure. It is demonstrated that oscillations can be excited under the beam current up to 4 A, the accelerating voltage being up to 4 kV at several frequencies within the range 0.6‑1.2 GHz in the quasi-continuous and continuous regimes.